Application of Service Quality Model in Education Environment - Ting Ding Hooi (Universitas Negeri Malang, 2016)
Most of the ideas on service quality stem from the West. The massive developments in research in the West are undeniable of their importance. This leads to the generation and development of new ideas. These ideas were subsequently channeled to developing countries. Ideas obtained were then formulated and used by these developing countries in order to obtain better approach in channeling service quality. There are ample to be learnt from the service quality model, SERVQUAL which attain high acceptance in the West. Service quality in the education system is important to guarantee the effectiveness and quality of education. Effective and quality education will be able to offer quality graduates, which will contribute to the development of the nation. This paper will discuss the application of the SERVQUAL model into the education environment.